Does operating performance increase post-takeover for UK takeovers? A comparison of performance measures and benchmarks - Powell, Ronan G.; Stark, Andrew W. (Journal of Corporate Finance, 2005)
Using several benchmarks and operating performance measures, the results from this paper suggest that takeovers completed in the UK over the period 1985 to 1993 result in modest improvements in operating performance. Using a matching procedure similar to that employed by Loughran and Ritter [J. Finance 52 (1997) 1823], in which benchmark firms are selected on the basis of several pre-takeover characteristics, the median increase in post-takeover performance for acquiring firms ranges from 0.13% per annum to a statistically significant 1.78% per annum, depending on the definition of operating performance used and choice of deflator. Using the same matching scheme in a Healy et al. [J. Financ. Econ. 31 (1992) 135] methodology, in which post-takeover performance is regressed on a combined target and acquirer pre-takeover performance, reveals larger improvements in operating performance, ranging from 0.80% to a statistically significant 3.1%, again depending on the definition of operating performance employed and deflator chosen. While there is some evidence that factors such as industrial relatedness and the removal of the target CEO have an impact on post-takeover performance, method of payment is found to have an insignificant impact.